THE INFLUENCE OF RELIGIOSITY AND SPIRITUALITY ON MENTAL HEALTH: PERSPECTIVES FROM PSYCHOLOGY IN CONTEMPORARY TIMES - Pessôa, Amanda Moreira; Pereira, Ana Patrícia Correia; Peixoto, Fabrisya Maria Saraiva; Ferreira, Greyciane Diniz; Gasparini, João Gabriel de Lima Santiago; de Oliveira, Mariana Pereira; de Araujo, Allan Diego Ricarte (Seven Editora, 2026)
Spirituality and religiosity are dimensions that have accompanied humanity throughout history, influencing how individuals deal with suffering and construct meaning in life. In recent decades, psychology has shown increasing interest in these phenomena, particularly in their relationship with mental health. This study, of a basic nature and qualitative approach, aims to analyze the positive and negative impacts of spirituality and religiosity on psychological distress, considering cultural, social, and individual aspects. The methodology consisted of a bibliographic review of scientific articles published in the SciELO, PePSIC, and Revista PPC databases. The results indicate that spirituality and religiosity can function as protective factors, promoting well-being, emotional resilience, and social support, especially when used as coping mechanisms in the face of adversity. On the other hand, rigid religious practices, marked by dogmas and moral punishment, may intensify psychological suffering, contributing to the worsening of conditions such as anxiety, depression, and psychotic disorders. Furthermore, conflicts between religious beliefs and therapeutic interventions may lead to resistance to treatment. In summary, based on the studies analyzed, it can be concluded that spirituality/religiosity is intrinsically present in the individual’s life and social context, constituting an important source of support in perceiving the world and coping with adversity. However, it is observed that while spirituality may represent support and subjective strengthening, when experienced or imposed excessively, it may be associated with psychopathological conditions, in which feelings of guilt and condemnation emerge as central elements of the experience.